The Extraction of White Ginger by Using Microwave Ultrasonic Steam Diffusion Method as the Essential Oil Substance - Angga Bahrul Alam; Suprapto Suprapto; Achmad Ferdiansyah; Ade Linda Autika (IPTEK Journal of Proceedings Series, 2018)
Zingiberene oil (C15H24)) is one of diversification products which has a high level of economic values. However, the rate of export number toward the export number has just recently attained 0,3% . Moreover the number of ginger oil as the export product does not fulfill the export standart, such as the Essential Oil Association of USA (EOA). This condition happens since the Hydro Distillation is applied as one of the method in refining process. Nevertheless, this method is considered the best method in refining process although it takes more time to gain the result of the refining process. Another extraction process is called as Microwave Distillation and Simultaneous Solid-Phase Microextraction (MDSS-PM). By applying this method, the total time estimation is reduced significantly, but the final result in refining process is not as good as by applying Hydro Distillation. This research applies Microwave Distillation as the extraction process of white ginger. Furthermore, this kinds of method is modified in such a way by adding optical ultrasonic (MUSDf). The variable used in this research is Steam Diffusion (SDf), Microwave Extraction (ME), Microwave Steam Diffusion (MSDf), Microwave Ultrasonic Steam Diffusion (MUSDf). Moreover, this result takes 30, 50, 70, 90 and 110 minutes. Furthermore, the extraction temperature is 90, 95, 100 dan 105oC. The final research shows that MUSDf is considered the best method in extracting the ginger oil with the yield result about 0,952% and zingiberene 6,38%. Hence, the total price for each essential oil costs Rp 17.964 by gaining 100oC of the optimum extraction temperature.